2013
DOI: 10.1108/17538351311312312
|View full text |Cite
|
Sign up to set email alerts
|

Employee perceived effects of workplace health promotion

Abstract: PurposeThe employees’ perspective is often disregarded in research regarding workplace health promotion (WHP). Experts’ opinions are prominent, stating employees’ benefits of WHP on the physical, mental, and social level. The purpose of this paper is to investigate which benefits and effects employees expect from WHP.Design/methodology/approachAs a current qualitative study indicates that employees also highlight cognitive aspects and prevention issues, a quantitative verification of this extended model was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…While these contributions were important, they did not translate to a change in men’s mental health and only made a partial contribution to the observed reduction in women’s psychological distress over time. Nevertheless, scope remains for comprehensive WHP to prove its worth as a universal intervention for mental health because direct interventions have evidence of success [ 47 ], and because they provide a pathway that raises the profile of mental health, thereby reducing its stigma [ 48 ]. When conducting naturalistic studies on mental health in work environments, a more integrated approach to employee health surveillance may be needed, which encompasses worker health promotion, protection and job-specific interventions.…”
Section: Discussionmentioning
confidence: 99%
“…While these contributions were important, they did not translate to a change in men’s mental health and only made a partial contribution to the observed reduction in women’s psychological distress over time. Nevertheless, scope remains for comprehensive WHP to prove its worth as a universal intervention for mental health because direct interventions have evidence of success [ 47 ], and because they provide a pathway that raises the profile of mental health, thereby reducing its stigma [ 48 ]. When conducting naturalistic studies on mental health in work environments, a more integrated approach to employee health surveillance may be needed, which encompasses worker health promotion, protection and job-specific interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Workplace health promotion programs (WHPPs) have become an increasingly popular means of promoting positive health behaviors in employees that are mutually beneficial to employers and employees [ 1 , 2 , 3 ]. Such programs can improve the overall health of the individual [ 4 , 5 , 6 , 7 ], increase physical activity [ 8 , 9 ], lead to small improvements in healthy weight status [ 6 , 10 ], have positive effects on dietary behaviors [ 3 , 11 ] and improve employee productivity [ 12 , 13 , 14 ]. Whilst there is overall support for the effectiveness of WHPPs, the reported extent to which such programs achieve lasting changes in behavior varies [ 10 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scientific reviews have shown that the design of successful WHPPs is a complex process and programs are most effective when they are: (1) based on scientifically valid constructs [ 17 , 18 , 19 , 20 , 21 , 22 ]; (2) tailored to the meet the needs of individuals [ 6 , 10 , 21 , 23 , 24 , 25 , 26 ]; and (3) perceived as both useful and enjoyable by participants [ 7 , 9 , 27 , 28 , 29 , 30 ]. Despite an abundance of practitioner research focused on validation of scientific constructs (e.g., the application of social cognitive theory [ 17 , 31 ] or behavioral strategies [ 21 , 32 ]), and objective outcomes of WHPP participation (e.g., changes in Body Mass Index (BMI) and nutritional consumption [ 8 , 10 , 11 , 33 ]); few studies have focused on employee perceptions of WHPPs associated with participation and engagement.…”
Section: Introductionmentioning
confidence: 99%
“…First, investment in the ‘social capital’ of the organisation [ 19 21 ] may contribute to workers’ perceptions of support [ 19 ] from their organisation because the employer shows care for their health and well-being [ 22 , 23 ]. The presence of WHP may also serve to reduce the stigma associated with reporting health-related issues or to enhance general health awareness among employees [ 23 ]. These emotional and cognitive effects have been linked to improved job satisfaction [ 18 , 24 ] and mental health [ 25 ].…”
Section: Introductionmentioning
confidence: 99%